(untitled) (Docentes 2.0 Journal, 2024)
People with disabilities have the right to be included in all educational levels, with free and effective social participation and equal opportunities. The objective of the investigative work was to develop a teacher training program that would provide the necessary foundations for the generation of inclusive environments. It comprises a mixed approach research, quantitative approach, inductive method, positivist paradigm, correlational and cross-sectional experimental design. The qualitative paradigm used individual constructivist interviews and an action research design—the selected sample comprised 60 preschool, primary, and secondary teachers. Two instruments were carried out, the first with a Likert scale to measure teaching deficiencies in inclusive education and the second with a semi-structured interview that measured learning from the training process and application in the classroom. As a result, teachers already have a clear outlook and the tools to generate inclusive environments within the classroom. The discussion shows that development strategies that contribute to good policies, practices, and inclusive cultures must be integrated through effective education. In conclusion, it is necessary to carry out new procedures with the authorities for teacher training from its initial stage in the inclusion process.